STRATEGI DINAS PEMBERDAYAAN PEREMPUAN, PERLINDUNGAN ANAK, DAN PEMBERDAYAAN MASYARAKAT KOTA PEKANBARU DALAM PENCEGAHAN KEKERASAN TERHADAP PEREMPUAN TAHUN 2024 - Rahmayanti, Aulia Novri; Wasillah, Asiah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Strategy is an art of achieving goals through three stages, namely formulation, implementation, and evaluation. A strategy must be designed to address issues that arise within a particular environment. The City of Pekanbaru consistently records the highest number of cases of violence against women compared to other regencies/cities in Riau Province. This study aims to identify and explain the strategies implemented in preventing violence against women. The main problem in this research is that Pekanbaru remains the area with the highest number of cases of violence against women in Riau Province. This study employs a descriptive qualitative approach to understand the strategies of the Office of Women’s Empowerment, Child Protection, and Community Empowerment (DPPAPM) of Pekanbaru City in preventing violence against women. Data were collected through interviews, observations, and primary documentation studies, as well as secondary sources including books, journals, and online references. The findings of this study, analyzed using Fred R. David’s strategic theory, show that the strategic role in this research is reflected in the coordination and synergy conducted by DPPAPM Pekanbaru City with various actors in efforts to prevent violence against women in 2024. The strategies are implemented based on the Strategic Plan (RENSTRA) of DPPAPM Pekanbaru City for 2023–2026. The preventive strategies include socialization activities, policy advocacy, and the execution of assistance and service duties. However, DPPAPM Pekanbaru City has not sufficiently designed clear programs and sub-programs within its Work Plan (RENJA), and clear indicators of success are not yet present in the 2024 Institutional Performance Report (LKJIP). Additionally, several internal and external factors influence the implementation of strategies for preventing violence against women. Keywords: Strategy, Prevention, Violence Against Women